Digital Human Resource Management and Its Effect on Human Resource Efficiency: Empirical Evidence from Manufacturing Companies in Batam, Indonesia - Ramon Zamora; Nurhayati Nurhayati; Sri Mulayti (FOUNDAE (Foundation of Advanced Education), 2026)
Digital transformation has fundamentally reshaped human resource management (HRM) practices in the manufacturing industry. Although many organizations have adopted Human Resource Information Systems (HRIS), their utilization often remains limited to administrative functions, thereby constraining their strategic potential. This study aims to examine the impact of Digital Human Resource (Digital HR) implementation on Human Resource Management efficiency in manufacturing companies. Employing a quantitative explanatory research design, data were collected from 40 human resource practitioners in manufacturing firms in Batam, Indonesia, using a structured questionnaire with a five-point Likert scale and purposive sampling technique. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results reveal that Digital HR implementation has a positive and significant effect on HRM efficiency (β = 0.670; p < 0.001), with a moderate explanatory power (R² = 0.449) and a substantial effect size (f² = 0.352). Multidimensional analysis indicates that the most significant improvements occur in process integration and decision-making readiness, rather than merely in administrative speed and data accuracy. These findings suggest that Digital HR functions not only as an operational tool but also as a strategic driver for enhancing organizational efficiency. This study contributes to the literature by validating the applicability of the Electronic Human Resource Management framework and the Technology Acceptance Model in a labor-intensive manufacturing context. Practically, the findings offer valuable insights for organizations seeking to optimize HR performance through digital transformation initiatives.